HUBUNGAN KEMANDIRIAN BELAJAR MATEMATIKA TERHADAP PRESTASI BELAJAR MATEMATIKA - Susanti, Dwi; Ola, Sania Latek (Jurnal Edumatic: Jurnal Pendidikan Matematika, 2024)
Quantitative research approach with the type of implementation survey research to find out whether mathematics learning achievement is influenced by student’s attitudes and learning independence. The sample in this study was 88 students in class IX at SMP Negeri 10 Tarakan. The distribution of student attitude questionnaires and student learning independence was carried out to collect data, then added to the midterm assessment document (PTS). F-test is used in analyzing data through SPSS 23.0. The results of this study indicate that there is a simultaneous influence between students' attitudes and independent learning on mathematics learning achievement, which is equal to 24.9%